PERFORMANCE ANALYSIS IN WIRELESS POWERED D2D- AIDED NON-ORTHOGONAL MULTIPLE ACCESS NETWORKS - Do, Dinh-Thuan (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
This paper examine how to integrate energy harvesting (EH) to non-orthogonal multiple access (NOMA) networks. Recently, device-to-device (D2D) underlaying licensed network is introduced as novel transmission mode to perform two nearby user equipment units (UEs) communicating directly without signal processing through the nearest base station (BS). By wireless power transfer, they can be further operational to D2D communications in which a UE may harvest energy from RF signal of dedicated power beacons (PB) to help EH assisted UEs communicate with each other or assist these UEs to communicate with the BS. In particular, we investigate outage and throughput performance in a scenario of D2D communications powered by RF signal where one UE may help other two UEs to exchange information with optimal throughput.